IMAN YANG MEMBUAHKAN MUJIZAT MENURUT MARKUS 5:21-42 - Setiawan, Tjutjun (Jurnal Teologi RAI, 2024)
The purpose of this article is to examine two consecutive events where two miracles occurred from two different people, one person begging Jesus for the benefit of another person and the other person for her benefit. The struggle of a father who has the position of head of a synagogue who is willing to experience potential ridicule due to his actions in worshiping Jesus, and the struggle of a woman who is desperate due to the illness she is suffering from and wants to get healing. The method used is qualitative with an expository approach to the verses in Mark 5:21-42, to find out how faith produces miracles as happened in these two incidents. The conclusion is that the faith that produces miracles is centered on Jesus Christ upon His will and mercy.